Perinatal Mortality in a Northwestern Nigerian City: A Wake up Call - Suleiman, Mohammed Bello; Mokuolu, Olugbenga Ayodeji (Frontiers in Pediatrics, 2014)
Background: In Nigeria, of the over 900,000 children under the age of five years that die every year, perinatal mortality is responsible for a little over 20%. Previous reports are largely from the southern part of the country. This is the first report of perinatal data from the northwest of Nigeria. Methods: a case control study of perinatal deaths in the three major public hospitals in Katsina metropolis was carried out to determine the pattern of perinatal deaths in the metropolis. Data were collected over a six week period on maternal socio-demographic, antenatal and delivery variables. Data were similarly obtained on neonatal profile and morbidities. Results: There were 143 perinatal deaths (94 stillbirths and 49 early neonatal deaths) out of 1104 live and stillbirths during the study period. The perinatal mortality rate was thus 130 per 1000 births with a stillbirth rate of 85 per 1000 births and an early neonatal mortality rate of 49 per 1000 live births. Stillbirths during the intrapartum period were twice as frequent as macerated stillbirths (2:1). Maternal factors significantly associated with perinatal deaths included chorioamnionitis, ruptured uterus, multiple gestation, medically induced delivery, prolonged labor, unbooked pregnancies, antepartum hemorrhage and prolonged rupture of membranes. Antepartum hemorrhage was the strongest determinant of perinatal death. Significant neonatal determinants were multiple gestation, severe birth asphyxia, apnea and necrotizing enterocolitis. Apnea was the strongest neonatal determinant. The majority (83.2%) of perinatal deaths were due to severe perinatal asphyxia (54.5%), normally formed macerated stillbirths (20.3%) and immaturity (8.4%). Conclusion: In conclusion, Perinatal Mortality in Katsina metropolis in northwest Nigeria is unacceptably high as we approach the timeline for the millennium development goals. Antepartum hemorrhage and severe perinatal asphyxia are major determinants.